Keeping cars from crashing. - Jones, W.D.
Adaptive cruise control is here, the first step toward systems that can help cars keep their distance on crowded highways. These adaptive cruise control (ACC) systems use laser beams or radar to measure the distance from the vehicle they are in to the car ahead and its speed relative to theirs. If a car crosses into the lane ahead, say, and the distance is now less than the preset minimum (typically a 1 or 2-second interval of separation), the system applies the brakes, slowing the car with a maximum deceleration of 3.5 m/s2 until it is following at the desired distance. If the leading car speeds up or moves out of the lane, the system opens the throttle until the trailing car has returned to the cruise control speed set by the driver
Keywords: Adaptive cruise control; Cruise control speed; Distance measurement; Laser beams; Leading car; Radar; Trailing car